Synthetic approaches to potent heterocyclic inhibitors of tuberculosis: A decade review - Dasmahapatra, Upala; Chanda, Kaushik (Frontiers in Pharmacology, 2022)
Tuberculosis (TB) continues to be a significant global health concern with about 1.5 million deaths annually. Despite efforts to develop more efficient vaccines, reliable diagnostics, and chemotherapeutics, tuberculosis has become a concern to world health due to HIV, the rapid growth of bacteria that are resistant to treatment, and the recently introduced COVID-19 pandemic. As is well known, advances in synthetic organic chemistry have historically enabled the production of important life-saving medications that have had a tremendous impact on patients’ lives and health all over the world. Small-molecule research as a novel chemical entity for a specific disease target offers in-depth knowledge and potential therapeutic targets. In this viewpoint, we concentrated on the synthesis of a number of heterocycles reported in the previous decade and the screening of their inhibitory action against diverse strains of Mycobacterium tuberculosis. These findings offer specific details on the structure-based activity of several heterocyclic scaffolds backed by their in vitro tests as a promising class of antitubercular medicines, which will be further useful to build effective treatments to prevent this terrible illness.